(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): How do leaders see their purpose during the organization and process of leading through time dimension? Purpose: The purpose of this paper is to expand knowledge in the field of time-sensitive inductive theory of leadership theory on the basis of selected examples of leaders. The aim of this paper is to show the importance of time-sensitive leadership theory on the basis of selected examples of leaders. Based on qualitative analysis we wish to identify the development and progress of representative leaders and provide organizational design of strategical leadership development context. Goals are: (1) Examine time-sensitive leadership theory; (2) Create a conceptual model of time-sensitive leadership theory based on the aggregation of the collected cases of leaders; (3) Provide organizational recommendations for the comprehensive development of leaders on the basis of multi-contingency organizational design model. Method: We used a qualitative research approach, namely biographical stories analysis of the conducted qualitative interviews. These were partly semi-structured interviews, partly in-depth interviews with the leaders and their followers and were based on the methodology of appreciative inquiry. Results: The study is well balanced, triangulation was implemented by incorporating the perspective of leaders and followers. The results were obtained on the basis of 20 interviews and 9 interviews with followers. Based on the answers to the research question a model was designed that shows the summarized statements which answer the research question and further connect other influences (values, personality orientation, environmental impact, follower) in addition to the effect of time. Organization: The findings provide useful recommendations for organizations, managers and human resources managers as we emphasize leaders’ own perspectives on the meaning of leadership and how they perceive their role over time. We present the impact of leaders’ own values, their personal attitudes, environmental influences. Society: Leadership is a reflection of the general social and economic changes or. dynamics in the social environment to which organization adjusts. Leading the organization has a direct impact on the stakeholders and wider social environment. All this is reflected in the leadership and the role of leaders, which is reflected in the personal maturation of leaders, milestones in their careers, learning new knowledge, personal experience, self-analysis, self-critical insights and responses of followers and is also reflected in the wider social environment. Originality: Our research focuses on the dimension of time in the development of leaders, which is neglected in theory. At the same time we combine the organizational design of a sustainable leadership development with concrete illustrations of examples of leaders. Limitations / further research: In our study there are several main limitations: (1) top managers dominate in our research sample;(2) all companies operate in the Slovenian environment; often at least partial ownership of the country; (3) there is a fairly homogenous age group of leaders; (4) there are a self-declared statements of leaders and followers of the impact of time (for the past). Milestones or triggers could be a separate research topic which is very interesting starting point to explore the development of leadership behavior, but it is an area that may be partially emotionally sensitive.